Severe Sleep Restriction Suppresses Appetite Independent of Effects on Food Intake-Regulating Hormones. (29th May 2020) - Radcliffe, Patrick; Whitney, Claire; Fagnant, Heather; Wilson, Marques; Smith, Tracey; Karl, J Philip
Abstract: Objectives: Several nights of moderate (4–5 hr/night) sleep restriction increases appetite and energy intake, and may alter circulating concentrations of food intake-regulating hormones. Whether more severe sleep restriction has similar effects is undetermined. This study aimed to determine the effects of severe, short-term sleep restriction on appetite and food intake-regulating hormones. Methods: Randomized, crossover study in which 18 healthy men (mean ± SD: BMI 24.4 ± 2.3 kg/m 2, 20 ± 2 yr) were assigned to three consecutive nights of sleep restriction (SR; 2 hr sleep/night) or adequate sleep (AS; 7–9 hr sleep/night) with controlled feeding and activity throughout the 3-day period. On day 4, participants consumed a standardized breakfast. Appetite ratings, and circulating ghrelin, peptide-YY (PYY), glucagon-like peptide (GLP-1), insulin, and glucose concentrations were measured before and for 4hr after the meal. Ad libitum energy and macronutrient intakes were then measured at a provided buffet lunch. Results: Median PYY (–21%) and GLP-1 (–14%) concentrations were lower, and median glucose (3%) concentrations were higher after SR relative to after AS (main effect of condition, P  < 0.05; condition-by-time interaction, P  = NS). Ghrelin and insulin did not differ between conditions. Mean hunger (–23%), desire to eat (–23%), and prospective consumption (–18%) ratings were all lower, and mean fullness (27%) ratings were higher after SR relative to after AS (main effect of condition, P  < 0.05; condition-by-time interaction, P  = NS). Ad libitum energy intake at the lunch meal was 14% lower after SR relative to after AS (–332 kcal [95% CI: −479, −185] P  < 0.001), but macronutrient composition did not differ. Conclusions: In contrast with reported effects of moderate sleep restriction, severe sleep restriction reduced appetite and energy intake. Appetite suppression was likely not due to the observed differences in food intake-regulating hormones as sleep-restriction induced reductions in PYY and GLP-1 concentrations would be expected to increase appetite. Funding Sources: US Army MRDC. Authors' views do not reflect official DoD or Army policy.